2010
DOI: 10.1007/s00270-010-0044-3
|View full text |Cite
|
Sign up to set email alerts
|

Safety Profile of Sequential Transcatheter Chemoembolization with DC Bead™: Results of 237 Hepatocellular Carcinoma (HCC) Patients

Abstract: DEBDOX chemoembolization is safe and small calibres do not result in increased complication rates compared with results of series using larger diameters of beads.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
94
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(105 citation statements)
references
References 42 publications
10
94
0
1
Order By: Relevance
“…grade of tumour necrosis (%) n = 28 No. complete necrosis (100 %) 5 (18) No. appropriate necrosis (C90 %) 2 (7) No.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…grade of tumour necrosis (%) n = 28 No. complete necrosis (100 %) 5 (18) No. appropriate necrosis (C90 %) 2 (7) No.…”
Section: Discussionmentioning
confidence: 99%
“…DC beads were loaded beforehand with doxorubicin at 37.5 mg/ml of bead suspensions of 300-500 lm (one vial of 2 ml) and 500-700 lm (one vial of 2 ml) [18,19]. By way of percutaneous femoral artery access, mesenteric arteriography was first performed to check for contraindications for chemoembolisation (portal thrombosis, arteriovenous shunt).…”
Section: Debdox Chemoembolisation Proceduresmentioning
confidence: 99%
“…Recently, chemoembolization using drug-eluting beads and radioembolization using yttrium-90 have been demonstrated to be efficient treatment options in patients with advanced HCC by outstanding locoregional effects, but [21] reported that the incidence of cholecystitis was 2.95-5.06 % after TACE for HCC using drug-eluting beads. The authors found that cholecystitis was observed more frequently in segmental embolizations compared with those of subsegmental distribution considered to be the result of inadvertent embolization of the cystic artery.…”
Section: Discussionmentioning
confidence: 99%
“…In recently published studies, doxorubicin-related systemic toxicity events and complications (alopecia, skin discoloration, mucositis, bone marrow suppression) were significantly reduced in the DoxMS group vs. conventional chemoembolization group [3,10]. In clinical practice, complications of DoxMSchemoembolization procedures, including liver abscess and liver failure [11,12], are different from the commonly observed postembolization syndrome due to postembolization ischemia [13]. In animal studies, DoxMS can cause necrosis of the hepatic arteries and normal tissues [5][6][7].…”
Section: Introductionmentioning
confidence: 96%